Poly(amide-triazole)s obtained by regioselective, microwave-assisted click polymerization of bio-based monomers - Fidalgo, Daniela Marina (2015)
The Cu(I)-catalyzed, microwave-assisted click polymerization of bio-based -azide--alkyne monomers afforded, with high regioselectivity, stereoregular poly(amide-triazole)s. The monomers were prepared starting from d-glucono-1,5-lactone as a renewable resource. The synthetic route involves the selective protection of this sugar lactone with formaldehyde to give a gluconic acid derivative, which was subjected to amidation of the carboxylic acid function with alkynylamines (2-propynyl, 3-butynyl, and 4-pentynylamines) and substitution of the primary hydroxyl group by azide. The regioselective click polymerization of these AB-type alkyne/azide monomers led to a series of linear biosourced poly(amide-triazole)s containing mostly (>95%) 1,4-disubstituted triazole linkages. In contrast, the thermal, metal-free click polymerization led to random distribution of 1,4- and 1,5-disubstituted triazoles in the polymer backbone. The length of the methylene chain linked to the amide of the monomer and the cycloaddition regioselectivity strongly affected the properties of the materials, mainly the Tg values, which were unexpectedly high.